Sphingosine 1-phosphate receptor 1 modulators exert neuroprotective effects in central nervous system disorders - Chen, Shouming; Wu, Lan; Lang, Bingchen; Zhao, Guoyan; Zhang, Wensheng (Frontiers in Pharmacology, 2025)
The sphingosine 1-phosphate (S1P) signaling pathway has important and diverse functions. S1P receptors (S1PRs) are involved in the regulation of lymphocyte trafficking, cardio-cerebral function, vascular permeability, and bronchiolar tone, and have been recognized as therapeutic targets for a variety of diseases. A number of drugs related to the S1P signaling pathway have been approved for clinical use in the treatment of multiple sclerosis, and many similar drugs are also currently being tested in clinical trials at various stages. It appears that S1PR modulators may not only be useful for the treatment of multiple sclerosis, but may also have therapeutic effects on other types of central nervous system (CNS) disorders. The present review focuses on the therapeutic potential of S1PR1 modulators for treating disorders of the CNS.